Fenomena Kesehjateraan Psikologis Pada Pegawai TASPEN: Studi Kualitatif di PT TASPEN (Persero) (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Psychological well-being refers to an individual’s ability to function optimally, maintain positive relationships, experience meaning in life, manage their environment, grow personally, and accept themselves fully. In modern work settings, psychological well-being has become a crucial factor influencing motivation, performance, and organizational sustainability. This study aims to explore the phenomenon of psychological well-being among employees at PT TASPEN (Persero) and examine how the organizational culture shapes the six dimensions of psychological well-being proposed by Ryff. A descriptive qualitative approach was employed through semi-structured interviews with seven informants across different job levels, complemented by observations and document analysis. Data were analyzed using Thematic Analysis. The findings indicate that positive relations and purpose in life are the strongest dimensions, supported by workplace solidarity and a sense of public service meaning. Conversely, autonomy, environmental mastery, and personal growth show disparities across job levels due to hierarchical structures and administrative burdens. This study highlights the need for more inclusive policies, equitable training opportunities, and streamlined procedures to enhance employees’ psychological well-being sustainably.